Melatonin attenuates methamphetamine-induced disturbances in mitochondrial dynamics and degeneration in neuroblastoma SH-SY5Y cells - Parameyong,A. (Wiley-Blackwell, 2015)
Methamphetamine (METH) is a psychostimulant drug that can cause toxicity and degeneration in the brain. The toxicity due to METH involves multiple pathways, including the mitochondrial-dependent death pathway. Several pieces of evidence have emphasized that the fragmentation of mitochondria into smaller structures plays some role in the cell-death process. In this study, we investigated the role of mitochondrial dynamics in METH-induced toxicity in human dopaminergic neuroblastoma SH-SY5Y cultured cell lines. In addition, the protective effect of melatonin against METH-induced toxicity was investigated. Our results show that METH significantly decreased cell viability and increased the levels of the mitochondrial fission protein, Fis1 and the Drp1 oligomer. However, the levels of the mitochondrial fusion proteins OPA1 and Mfn1 did not change in METH-treated cells. Melatonin can reverse the toxic effects of the METH-induced reduction in cell viability and the production of the Fis1 protein and the Drp1 oligomer. Moreover, the morphological alteration of mitochondria was investigated in METH-treated cells in the presence of melatonin using transmission electron microscopy (TEM). At 24 hr after METH exposure, typical cell shrinkage was observed in SH-SY5Y cells. Mitochondria were fragmented into small globular structures in a large proportion of METH-treated cells, but tubular networks of mitochondria were present in large proportions of control-untreated cells and METH-treated cells in the presence of melatonin. The results of the present study demonstrate the potential of melatonin to reduce cell death and restore mitochondrial function in neurons affected by METH-induced toxicity. © 2013 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd.